Importation of hybrid human-associated Trypanosoma cruzi strains of southern South American origin, Colombia (2016)
We report the characterization of Trypanosoma cruzi of southern South American origin among humans, domestic vectors, and peridomestic hosts in Colombia using high-resolution nuclear and mitochondrial genotyping. Expanding our understanding of the geographic range of lineage TcVI, which is associated with severe Chagas disease, will help clarify risk of human infection for improved disease control. © 2016, Centers for Disease Control and Prevention (CDC). All rights reserved.